A University Students’ Intentions to Use Slack: An Integrated Approach of TAM and SDT - Rakha Athallah Syahputra; Osly Usman (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study examines university students’ intentions to adopt Slack, a real-time communication platform, by integrating the Technology Acceptance Model (TAM) and Self-Determination Theory (SDT). The research focuses on how competence, perceived usefulness, and perceived ease of use influence students’ attitudes and actual system usage. Data were collected from 185 university students at Universitas Negeri Jakarta who used Slack for academic purposes. Structural Equation Modeling (SEM) analysis revealed that competence significantly impacts perceived usefulness and ease of use, which in turn positively affect students’ attitudes toward using Slack. Additionally, attitudes strongly predict actual system usage. The results indicate that students with higher competence and positive perceptions of Slack’s utility and ease of use are more likely to integrate it into their academic activities. This study underscores the importance of intrinsic motivation and user-friendly design in promoting the adoption of digital tools for collaborative learning, offering actionable insights for educators and institutions aiming to enhance academic productivity through technology.